Pemodelan Regresi Logistik dalam Penentuan Faktor-Faktor yang Berpengaruh Terhadap Penyakit Jantung Koroner - Hoyyi, Abdul (JURNAL SAINS DAN MATEMATIKA, 2011)
Coronary heart disease (CHD) is a health problem and is one of the leading causes of the death in both developed and developing countries. Thereby it needs to analyze the factors which influence it. Some factors supposedly influence the CHDâ€™s patients are cholesterol levels, low density lipoprotein levels, high density lipoprotein levels, triglyceride levels, systolic blood pressure, diastolic blood pressure and gender. The data used are secondary data from the medical records of CHDâ€™s patients and general check-up records of the healthy people in a hospital in Yogyakarta. The analysis used in this research is binary logistic regression response with dichotomous dependent variables. Of the seven suspected factors, only four significant influence factors namely cholesterol levels, high-density lipoprotein levels, systolic blood pressure and diastolic blood pressure. Â Keywords: CHD, logistic regression